Knowledge of proprietary and generic drug names among hospital prescribers: time to mandate generic prescribing?. Issue 8 (August 2017) - Davis, Joshua S.; Barrett, Thomas; Harris, Lisa
Abstract: Although medical students are taught clinical pharmacology using generic drug names, prescribing in hospitals often uses brand names. As a result, junior doctors may be prescribing drugs without knowing their nature or mode of action. We carried out a knowledge survey of 81 medical students and doctors at a 650‐bed Australian teaching hospital to assess their knowledge of common drugs when given the brand name. We identified 20 commonly prescribed drugs and their brand names based on current hospital inpatients. No participant was able to provide the generic name, class or mode of action for all 20 drugs, with an average of 8.3 of 20 and 6.3 of the 10 most common drug names correctly identified. These data support calls to mandate prescribing using generic rather than brand names of drugs in hospitals.